THE HEALTH PERCEIVED, SOCIAL SUPPORT, AND ITS IMPACT TOWARD SELF-MANAGEMENT OF ELDERLY WITH TYPE 2 DIABETES MELLITUS - Nazliansyah Nazliansyah; Septy Nur Aini (NURSE: Journal of Nursing and Health Science, 2025)
Background: Diabetes mellitus type 2 requires consistent self-management to prevent complications, particularly among older adults who are vulnerable to disease progression. However, the determinants of diabetes self-management at the primary healthcare level remain insufficiently explored. This study aimed to identify factors associated with self-management among elderly patients with type 2 diabetes mellitus in Belitung District. Method: A quantitative cross-sectional design was employed involving 127 participants aged 60–69 years selected through multistage random sampling from five primary health centers. Data were collected using validated questionnaires and analyzed using Pearson and point-biserial correlation tests. Results: The results showed that treatment (r = 0.376; p < 0.001), diabetes knowledge (r = 0.260; p = 0.003), perceived benefits (r = 0.183; p = 0.039), self-efficacy (r = 0.308; p < 0.001), and social support (r = 0.314; p < 0.001) were significantly associated with diabetes self-management. Age, gender, education, duration of diabetes, and income were not significantly related)]. Conclusion: These findings highlight the importance of psychosocial and treatment-related factors in improving diabetes self-management among elderly patients at the primary care level. Strengthening education, self-efficacy, and social support may enhance sustainable self-management practices Keywords : Type 2 Diabetic mellitus, Self-management, Self-Efficacy